2017
DOI: 10.1007/s13762-017-1602-x
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic activity as an indicator of regeneration processes in degraded soil reclaimed with various types of waste

Abstract: Soil material sampled from a reclamation experiment established in a former ''Jeziórko'' Sulphur Mine was analysed. The reclamation was carried out on a soil-less substrate with a particle size distribution of slightly loamy sand characterised by high acidity and poor sorption capacity. The different variants of the experiment consisted in the addition of post-flotation lime, mineral fertilisation, sewage sludge, and mineral wool to the reclaimed soil-less substrate. Next, the plots prepared in this way were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 26 publications
1
22
0
2
Order By: Relevance
“…Scientific literature suggests that the use of sewage sludge in cultivation of energy crops increases soil biological activity (Ruf et al 2018). The increased soil enzymatic activity confirms that, as a result of mineralization of organic matter, sewage sludge makes macronutrients available to plants (Joniec 2018). The obtained results of the authors' own research have been confirmed by other authors (Symanowicz et al 2018).…”
Section: Soil Enzymessupporting
confidence: 61%
“…Scientific literature suggests that the use of sewage sludge in cultivation of energy crops increases soil biological activity (Ruf et al 2018). The increased soil enzymatic activity confirms that, as a result of mineralization of organic matter, sewage sludge makes macronutrients available to plants (Joniec 2018). The obtained results of the authors' own research have been confirmed by other authors (Symanowicz et al 2018).…”
Section: Soil Enzymessupporting
confidence: 61%
“…Biostability is a key feature in biosolids to evaluate their use as organic amendment in soils. In the last decade, studies in soils with various organic amendments have focused on using biological properties for their sensitivity to change, as indicators of the dynamics of organic matter transformation, nutrient cycling, stress and regeneration processes [66,[97][98][99]. Therefore, it was important to evaluate biological parameters for 1 year to establish indicators of quality and functionality of biosolids that have been added to soils, and thus be able to elucidate the positive or negative effects of adding these biosolids to soils before their application.…”
Section: Biological Characterisation Of Biosolidsmentioning
confidence: 99%
“…URS is an enzyme that catalyses the hydrolysis of urea into carbon dioxide and ammonia by acting on the C-N bonds of different peptides [129]. Therefore, the activity of the URS is of great importance in the biotransformation processes of nitrogenous organic compounds [99]. The values reached for the activity of URS in the biosolids analysed at different times of the year ranged from 109.82 to 194.55 mg N-NH 4 + kg −1 dry biosolids h −1…”
Section: Biological Characterisation Of Biosolidsmentioning
confidence: 99%
“…Arıtma çamuru ilavesi ile bitki uygulaması kombinasyonu, toprağın fizikokimyasal durumunu genel olarak iyileştirdiği gibi, toprak kalitesinin bir göstergesi olarak kabul edilen enzim aktivitesi seviyelerini de önemli ölçüde arttırmıştır. Eski kükürt madeni topraklarının farklı atıklarla ıslahının incelendiği bir çalışmada, yapılan uygulamaların topraklardaki katalaz, proteaz ve üreaz aktivitesini önemli derecede arttırdığı ve en büyük etkinin, arıtma çamurunun tek başına veya diğer atıklarla birlikte uygulandığı topraklarda belirlendiği tespit edilmiştir (Joniec, 2018).…”
Section: Arıtma çAmurlarının Tarım Arazilerinde Kullanımıunclassified